2017
DOI: 10.1016/j.psychres.2017.07.065
|View full text |Cite
|
Sign up to set email alerts
|

Active suicidal ideation during clinical antidepressant trials

Abstract: Suicidal patients are often excluded from clinical trials of psychiatric medications and from investigations using neurobiological techniques. To evaluate the presence, impact, and stability of active suicidal ideation (SI) across a range of antidepressant trials, we reviewed 14 clinical trials conducted in patients with either major depressive disorder (MDD) or bipolar disorder (BD) (N=269). Active SI at any time point in the clinical trial was identified and linked to participation in other research procedur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…In patients with comorbid substance use disorders, easing access to treatment, providing counseling, and social support in addition to the treatment of depression is recommended [15]. However, as patients with SI are often excluded from most antidepressant trials, limited data are available to study their disease or treatment characteristics [18].…”
Section: Introductionmentioning
confidence: 99%
“…In patients with comorbid substance use disorders, easing access to treatment, providing counseling, and social support in addition to the treatment of depression is recommended [15]. However, as patients with SI are often excluded from most antidepressant trials, limited data are available to study their disease or treatment characteristics [18].…”
Section: Introductionmentioning
confidence: 99%
“…This misconception is not limited to ethics committees; a survey of 28 suicide researchers demonstrated widespread concern that research participation in general might exacerbate suicidality. In fact, data from our studies show the exact opposite [91]. Clearly, the continued perpetuation of the iatrogenic potential of suicide risk has hampered suicide research, particularly approval by ethics committees.…”
Section: Discussionmentioning
confidence: 89%
“…Another study examining clinical bipolar disorder research studies found no completed suicides or suicide attempts in 11 placebo-controlled trials for an acute manic episode; in contrast, the researchers found two suicides and eight suicide attempts in four placebo-controlled trials to prevent manic or depressive episodes, all of which occurred in the active compound group [90]. Another retrospective study found that emergent suicidal ideation during clinical trials was short-lived and not exacerbated by research procedures [91]. Perhaps most importantly, in 24 pediatric trials of selective serotonin reuptake inhibitors (SSRIs), which carry a black box warning of suicide risk, there were no deaths from suicide in 4582 patients [92].…”
Section: Discussionmentioning
confidence: 99%
“…However, few patients with MDD receive these agents due to Food and Drug Administration indication, declining use, adverse effects, and frequent monitoring 42,43. In addition, traditional antidepressant medications were not commonly studied in patients with suicidal behaviors or those deemed to be at high risk for suicide; therefore, conclusions about their antisuicidal effects are limited and likely related to overall mood improvement 7…”
Section: Discussionmentioning
confidence: 99%
“…The black box warning of antidepressants for suicidality among children and adolescents may also present as barriers for using these agents. Furthermore, most clinical trials of antidepressants exclude suicidal patients, which limits generalizability of the results of efficacy trials for patients who display behaviors of self-harm 7. Nonantidepressants, such as lithium or clozapine, have demonstrated benefit in reducing suicidal behaviors; however, these outcomes were not demonstrated in the emergent setting 8.…”
Section: Introductionmentioning
confidence: 99%